Edited for Instagram: the impact of curated social media influencer profiles on self-representation - Ranooe, Lijeng. P. (My University, 2022)
The increased popularity of social media in the past decades has turned it into an integral function of online communication and presentation around the world. This has led to the prevalence of social media influencers that can impact society through their actions and opinion thus having an impact on social media usage. This research discusses topics surrounding whether social media influencers impact the Instagram content of active social media users. The research has considered the social media patterns and choices of active Instagram users. This is loosely based on the hypothesis that active social media users in South Africa use social media to have as many followers as possible or even become social media influencers themselves. The study revealed that although influencers set an idealized standard for content quality; active Instagram users do not view it as necessary to create content that has that quality despite the pressures and standards that social media presents; which most users cannot keep up with. Although this research cannot be a conclusive representation of all Instagram users in South Africa it depicts a different perspective about the use of social media that broadens it to be more diverse than numbers and interaction. There is a call for authentic representation of the regular realities that society faces for the normal to be acceptable. It is predictive of a shift towards the intent of using social media applications being geared towards the intent of its use for each user. The study also indicated that the relationship that users have with social media can directly correlate to how they perceive the content of others.
A research report submitted in partial fulfilment of the requirement for the Master’s Degree in Digital Arts to the Faculty of Humanities, University of the Witwatersrand, 2022